Student Motivation to Wear the Veil in Perspective of Fatwa Tarjih Muhammadiyah - Mardiyah Hayati; Dewi Urifah; Niswatun Hasanah (EDUKASI : Jurnal Pendidikan Islam (e-Journal), 2023)
This research is related to the motivation of some Muhammadiyah University students who use the veil, namely a cloth that covers the face or part of a woman's face; this makes these students different from other students. This study uses field research. The data collection techniques used were observation, documentation and in-depth interviews with several veiled students, then looking for other data sources in some literature about the headscarf, especially the Muhammadiyah tarjih fatwa regarding the headscarf. Researchers perform data reduction, data display, and drawing conclusions or verification in analyzing data. The results of this study concluded that the motivation of veiled female students at the Muhammadiyah University of Mataram was more caused by internal factors, namely wanting to try to improve themselves, avoid slander, and maintain the guidance given by Allah SWT. Thus, the motivation of the veiled students does not conflict with Muhammadiyah's views, but in the Muhammadiyah fatwa regarding the veil, there is no call to use the veil. Â